The Gratton effect remains after controlling for contingencies and stimulus repetitions - Blais, Chris; Stefanidi, Aikaterini; Brewer, Gene A. (Frontiers in Psychology, 2014)
The Gratton effect, the observation that the size of the Stroop effect is smaller following an incongruent trial compared to a congruent trial, is one pivotal observation in support of the conflict-monitoring hypothesis. Previous reports have demonstrated that non-conflict components, such as feature binding, also contribute to this effect. Critically, Schmidt and De Houwer (2011) report a flanker task and a button-press Stroop task suggesting that there is no conflict adaptation in the Gratton effect; it is entirely caused by feature binding. The current investigation attempts to replicate and extend this important finding across two experiments using a canonical four-choice Stroop task with vocal responses. In contrast to Schmidt and De Houwer, we observe reliable conflict adaptation after controlling for feature binding. We argue that the overall strength of conflict is critical for determining whether a conflict adaptation component will remain in the Gratton effect after explaining binding components.